Financial Performance: The Role of Corporate Social Responsibility and Good Corporate Governance - Dewi, I Gusti Ayu Ratih Permata; Yuliana, Ni Made Mita; Yoga, I Gusti Agung Prama (GOVERNORS, 2025)
This study will analyze the influence of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) on the financial performance of companies listed on the IDX from 2021-2023. This study uses a quantitative and purposive sampling method, resulting in 69 samples from 23 companies. Secondary data was collected through documentation and analyzed using panel data regression. This study shows that CSR contributes positively but not significantly to financial performance. Then, the size of the board of directors and the audit committee in GCG contributes negatively but not significantly; finally, the board of commissioners contributes positively but not significantly to financial performance. Based on the results of the study, it is recommended that investors pay more attention to CSR disclosure as a consideration for investment. Companies are also expected to consistently carry out and report CSR and GCG activities even though they do not have a significant impact on profitability because this can increase investor confidence. For further research, adding other variables such as institutional ownership, managerial, and company size, as well as extending the research period and using more financial ratios to obtain more comprehensive results, is recommended.